CUSTOMER ORIENTATION AMONG RURAL HOME STAY OPERATORS IN MALAYSIA - KAYAT, KALSOM (ASEAN Journal on Hospitality and Tourism, 2007)
Based on earlier writings and research in the fields of total quality management, service quality and marketing which suggest understanding customer needs is a pre-requisite to satisfactory service delivery, a study was undertaken to understand and analyze customer orientation among the home stay operators in Malaysia. Data was collected from 142 respondents who operate home stay programs in 10 rural areas in Peninsular Malaysia using structured survey questionnaires. Findings from the study indicate that rural home stay operators place utmost importance on customer satisfaction as long as it is within their means and their boundaries of traditional customs. What needs to be improved on is their capability so that they are able to identify the expected quality of service of the visitors and so that they are able to fulfil this expected quality of service.